2003
DOI: 10.1088/0953-8984/15/48/014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triplet attractions on the phase diagram of suspensions of charged colloids

Abstract: We study, by simulation, the effect of attractive triplet interactions on the phase behaviour of suspensions of charged colloidal particles at low ionic strength, i.e. in the regime where the pair interactions are purely repulsive. We use the pair and triplet interactions that were obtained recently from a numerical, nonlinear Poisson-Boltzman study (Russ et al 2002 Phys. Rev. E 66 011402). Our simulations tentatively explain, for the first time, experimental observations of a rather large density difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
5
19
0
Order By: Relevance
“…Of these observations (ii) has already been confirmed by Dobnikar et al [3] in the truncated-point Yukawa system, However, whether observations (i) and (iii) are supported by the earlier study cannot be answered since the Lindemann criterion used in [3] is not suited to resolve the relative stability of the BCC and FCC phases. Finally, we like to stress that (i), the instability of the BCC phase, was also found recently in our simulation study where the effect of triplet attractions on the phase diagram of charged colloids was investigated [6]. The effect of many-body interactions on the phase behaviour is a destabilization of the BCC phase, which should be observable in experiments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Of these observations (ii) has already been confirmed by Dobnikar et al [3] in the truncated-point Yukawa system, However, whether observations (i) and (iii) are supported by the earlier study cannot be answered since the Lindemann criterion used in [3] is not suited to resolve the relative stability of the BCC and FCC phases. Finally, we like to stress that (i), the instability of the BCC phase, was also found recently in our simulation study where the effect of triplet attractions on the phase diagram of charged colloids was investigated [6]. The effect of many-body interactions on the phase behaviour is a destabilization of the BCC phase, which should be observable in experiments.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, preliminary free energy calculations with x = 1.77 showed a stable BCC phase at 1/κσ = 0.4. Destabilization of the BCC phase was also found recently in a simulation study that investigated the effect of triplet attractions on the phase diagram of charged colloids as a first-order many-body correction to pairwise additivity [6]. It is also worth mentioning that the fluid-FCC phase boundary above the second triple point follows closely the fluid-BCC phase boundary of the non-truncated Yukawa system.…”
Section: Resultssupporting
confidence: 71%
“…This discussion was fueled by theoretical results of attractive three-body interactions 13,14 and experiments that show densitydependent pair interactions 15,16 ͑signaling that the underlying interaction is not pairwise͒. In our earlier work, 23,24 we studied the effect of attractive three-body interactions on the phase behavior of charged colloids and found that they give rise to broad fluidfcc and bcc-fcc coexistence regions. [17][18][19] What remains to be less clear-cut is the effect of the many-body interactions on the phase behavior of charged colloids.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 To this end, we develop an efficient simulation method for the highly asymmetric primitive model. 23,24 To this end, we develop an efficient simulation method for the highly asymmetric primitive model.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of triplet attractions also affects the relative stability of fcc and bcc crystals. A brief version of this paper was published elsewhere [28].…”
Section: Introductionmentioning
confidence: 99%